Formação de professores envolvendo a prova matemática: um olhar sobre o desenvolvimento profissional - Grinkraut, Melanie Lerner (2009)
This present study looked into the professional development of two Mathematics teachers, as a result of their participation in a research project called AProvaME (Argumentation and Proof in Mathematics Education), carried out by Pontifícia Universidade Católica (PUC) of São Paulo. Besides participating as researchers in the project, these teachers were studying for their Professional Mathematics Education Master s degree and teaching in public high schools. The present research monitored their processes during two years, while they were developing, implementing and evaluating learning situations in Geometry, which searched for the proof construction from the students, by the integration of Cabri-Géomètre software in the activities. According to the AProvaME proposal, during their participation in the project, these teachers were involved in a context, where group practices, as reflection, collaboration and investigation, besides others related to teaching experience, as the reflection on their own practice, were developed. This study aimed to check to what extent the teacher s participation in this project, propitiated a change in their conceptions and practices, influencing their professional development. In order to reach this goal, the theoretical references articulated the theories about professional development, the proof and the use of technological resources in the educational environment. The research s methodology was focused in the qualitative investigation, using the case study, considered as analytic, investigating both teachers as multiple cases . These two teachers passed through different processes in their courses, while participating in the AProvaME, which occurred partly because their own personal characteristics, their experience as students and teachers and what they had lived in the project, leading to different evidences of professional development. To one of them, the participation in a group, where practices as reflection, collaboration and investigation were developed, turned to be catalyst to promote changing in conceptions and practices, reflecting in his professional development. The other one, who was not submitted to these practices in such a strong way, could not break with previous conceptions and practices. In spite of this, the results already suggest that to both teachers the participation in the project lead them to broaden their mathematical knowledge. They also became aware of the possibilities of computers use in the learning activities and the difficulties which involves this integration. In the end of the AProvaME, it was verified the importance given by the teachers to the experienced process, in a way that they started to take into account the students development mathematical skills, the reasoning involved in the proof process, even if many times the students were not able to reach the required mathematical formalization. This study presents indications that the way how researches projects are conducted, included in processes of continuity teacher s education programs, where occur group practices, such as reflection, collaboration and investigation, could establish excellent opportunities of professional development for the teachers that attended the project. However, individual and personal factors can also interfere, because the group does not always benefit to all the people involved. This study tried to reveal ways to rethink formative processes, which can result in professional development